1999
DOI: 10.1002/(sici)1097-4644(19991101)75:2<258::aid-jcb8>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide prevents apoptosis of human endothelial cells from high glucose exposure during early stage

Abstract: Hyperglycemia is a major cause of diabetic vascular disease. High glucose can induce reactive oxygen species (ROS) and nitric oxide (NO) generation, which can subsequently induce endothelial dysfunction. High glucose is also capable of triggering endothelial cell apoptosis. Little is known about the molecular mechanisms and the role of ROS and NO in high glucose-induced endothelial cell apoptosis. This study was designed to determine the involvement of ROS and NO in high glucose-induced endothelial cell apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…NO may attenuate H 2 O 2 production by inducing catalase. In agreement with this idea, it has been demonstrated that NO decreases H 2 O 2 production induced by lectin in human polymorphonuclear leukocytes, reduces H 2 O 2 generation by TNF-␣ treatment of carcinomas, inhibits H 2 O 2 production by high glucose exposure in HUVEC, and decreases the degree of elevation of H 2 O 2 induced by insulin-like growth factor I in cultured rat aortic smooth muscle cells (55)(56)(57)(58). H 2 O 2 has been shown to act as a signaling molecule that activates transcriptional factor NF-B, which then mediates the expression of proinflammatory cytokines in macrophages stimulated by LPS (59 -61).…”
Section: Discussionmentioning
confidence: 67%
“…NO may attenuate H 2 O 2 production by inducing catalase. In agreement with this idea, it has been demonstrated that NO decreases H 2 O 2 production induced by lectin in human polymorphonuclear leukocytes, reduces H 2 O 2 generation by TNF-␣ treatment of carcinomas, inhibits H 2 O 2 production by high glucose exposure in HUVEC, and decreases the degree of elevation of H 2 O 2 induced by insulin-like growth factor I in cultured rat aortic smooth muscle cells (55)(56)(57)(58). H 2 O 2 has been shown to act as a signaling molecule that activates transcriptional factor NF-B, which then mediates the expression of proinflammatory cytokines in macrophages stimulated by LPS (59 -61).…”
Section: Discussionmentioning
confidence: 67%
“…Salt and co-workers reported that chronic elevated glucose reduced eNOS activity in the absence of changes in eNOS phosphorylation [30]. Ho and colleagues reported that eNOS protein expression in HUVECs was up-regulated by acute high glucose (33 mmol/l) exposure for 2 to 6 h, and gradually decreased after longer exposure [31]. Conversely, Cosentino et al have reported the up-regulation of eNOS expression after the exposure of human aortic ECs to 22 mmol/l glucose for 5 days [11].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for increased NO production under hyperglycemic conditions is shown, for example, by the increase in NO release in endothelial cells exposed to high glucose levels (9,16,18). Furthermore, indices of NO production such as nitrate and nitrite levels are elevated in experimentally induced models of diabetes (3,31).…”
Section: Discussionmentioning
confidence: 99%